LIMITATIONS ON THE USEFULNESS OF PRICE LEVEL ADJUSTMENTS. - Dohr, James L. (The Accounting Review, 1955)
Abstract The article presents comparative rather than absolute limitations, a problem that faces accounting, and deals with purchasing power measurements in accounting. In recent times, two basic economic fears, namely, inflation and deflation have been developed which involve concern about the purchasing power of the dollar, and its lack of monetary stability or shifting of the price level. The general price index, or any one of its broad subdivisions, is admittedly no more than a very general indication of what "package" of goods and services a given quantity of money will buy under certain conditions of time and place. The price index blends indiscriminately the effect of monetary factors with such factors as output, technology, wage bargaining, etc. The problem of inflation may be delimited and treated as involving determination of the cost of goods delivered to customers, determination of the cost of utilization of long-term assets, and measurement for administrative and other purposes of return on capital investment.